2019
DOI: 10.1177/0391560319882231
|View full text |Cite
|
Sign up to set email alerts
|

A review of hypogonadotropic hypogonadism cases followed up in our clinic in the last decade

Abstract: Introduction: The aim of the present study was to evaluate, with this retrospective study, the patients with hypogonadotropic hypogonadism, who were followed up in our clinic in the last decade and were reviewed in terms of the incidence of the disease, diagnostic methods and differential diagnoses, treatment modalities, fertility rates, and treatment success. Methods: After a very careful differential diagnosis, 81 patients (1.5% of infertile men presenting to the outpatient clinic) were diagnosed with hypogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(14 reference statements)
2
5
1
Order By: Relevance
“…The most important issue when using hCG to treat MHH and to achieve the desired outcomes was the dose and duration of treatment. 24 In the present study, the group was treated with CC at 25 mg daily and hCG at an average dose of 5000 IU administered twice weekly (i.m. or s.c.).…”
Section: Discussionmentioning
confidence: 99%
“…The most important issue when using hCG to treat MHH and to achieve the desired outcomes was the dose and duration of treatment. 24 In the present study, the group was treated with CC at 25 mg daily and hCG at an average dose of 5000 IU administered twice weekly (i.m. or s.c.).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary adrenal deficiency can be assessed by measuring morning cortisol and ACTH. Because sex steroids are necessary for growth, performing a bone age measurement should be considered in all hypogonadal patients, who may have delayed bone age compared with chronologic age [ 3 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spratt et al (33), reported that patients with partial/normal nocturnal LH pulses had larger testicular volume (4 mL) compared with those without LH pulses. We have reported in a currently published study (34); there are several treatment methods for patients with CHH. 1.…”
Section: Testosterone Replacement Therapy (Trt)mentioning
confidence: 99%
“…Compared to the literature, our series has the longest follow-up, and highest pregnancy and success rates. This can be explained by our approach that included persuading the patients to undergo long-term treatments, and increasing the dose of medicine without hesitation (34).…”
Section: Testosterone Replacement Therapy (Trt)mentioning
confidence: 99%